Spiralok exhibition display (circa 1950) - Hercules Incorporated (1950)
General view of an exhibition display for Spiralok cartridges manufactured and sold by the Hercules Powder Company for use with Vibrogel explosives and Vibrocap blasting caps. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Hercules Incorporated; Corporations; Chemical industry; Explosives; Explosives industry; Trade shows; Advertising; Advertising, Industrial